Physical Education Lecture Evaluation Studies in Cognitive, Affective, and Psychomotor in Students - Nur Muhamad Hildan; Dewi Susilawati; Dinar Dinangsit (JUARA : Jurnal Olahraga, 2022)
Evaluation is an activity to collect information about the work of something, which is then used to determine the suitable alternative in making a decision. This study aims to assess the evaluation of lectures in terms of cognitive, affective, and psychomotor. The subject of the research conducted by researcher interviewed four students. This research is qualitative research using a qualitative descriptive method. Study results The results of observations, interviews and documentation that the evaluation of lectures in terms of cognitive, affective, and psychomotor PGSD Penjas students have advantages and disadvantages, especially in terms of lecturers and students who have to work together in lectures that run smoothly